2002
DOI: 10.1152/japplphysiol.00224.2002
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of diet on leptin, energy intake, and activity in a model of diet-induced obesity

Abstract: This study investigated the effect of long-term high-fat sucrose (HFS) or low-fat complex-carbohydrate (LFCC) diet consumption on leptin, insulin, fat cell size, energy intake, and markers of activity to ascertain the role that leptin plays in long-term energy balance in a model of diet-induced obesity. Female Fischer 344 rats were fed either a HFS or LFCC diet ad libitum for a period of 20 mo. Measurements of leptin concentration, insulin concentration, and adipocyte size were performed at 2 wk, 2 mo, 6 mo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 49 publications
(50 reference statements)
3
37
0
Order By: Relevance
“…One characteristic feature of "insulin resistant" adipocytes is an increase in adipocyte cell size (29,47,48). Analysis of the adipocyte cell size showed that, as expected, the average size of the adipocytes in the HFD group was significantly larger than in the ND mice, a result reported previously by others in similar rodent models of dietary-induced obesity (22,29,35,44). Compared with the HFD-lean group, the relative distribution of adipocytes according to size was similar to that of the ND group, whereas the HFD-fat group showed a higher proportion of larger-sized adipocytes.…”
Section: Discussionsupporting
confidence: 63%
“…One characteristic feature of "insulin resistant" adipocytes is an increase in adipocyte cell size (29,47,48). Analysis of the adipocyte cell size showed that, as expected, the average size of the adipocytes in the HFD group was significantly larger than in the ND mice, a result reported previously by others in similar rodent models of dietary-induced obesity (22,29,35,44). Compared with the HFD-lean group, the relative distribution of adipocytes according to size was similar to that of the ND group, whereas the HFD-fat group showed a higher proportion of larger-sized adipocytes.…”
Section: Discussionsupporting
confidence: 63%
“…However, it has been demonstrated that leptin is also synthesized by the gastric chief cells and release of gastric leptin occurs 15 min after refeeding in fasted rat (39). A high-fat sucrose (HFS) diet resulted in hyperleptinemia and hyperinsulinemia before adipocyte size was observed to increase (40). It was interesting to note in this study that high fat diets containing primarily sugar cane and psyllium resulted in lower plasma leptin concentrations when compared to the high-fat diet alone or high fat diet containing 10% cellulose.…”
Section: Discussionmentioning
confidence: 99%
“…Energy from fat has a larger effect on body-weight gain than has energy from non-fat sources (12,14,22,49,106,150,151) . Diet-induced thermogenesis is the energy for digesting, absorbing and storing nutrients and produces a loss of energy for the body which is 2 -3 % for fats, 25 -30 % for proteins and 6 -8 % for carbohydrates.…”
Section: Physiological Mechanisms Of High-fat Diet-induced Obesitymentioning
confidence: 99%